COMPARATIVE STUDY ON THE SYNTHESES OF CARBON NANOMATERIALS USING POLYETHYLENE AND RISK HUSK AS CARBON PRECURSOR - Kure, Nicodemus; Daniel, Isaac Hyuk; Machu, B. U.; Bello, I. A.; Ansnawi, M. (FUDMA JOURNAL OF SCIENCES, 2020)
The study compares the syntheses of carbon nanostructures (CNS) using polyethylene (PE) and Rice husk (RH) as carbon precursor via commercial microwave oven at 2.45 GHz. The Microwave energy offers the requisite temperature for catalytic disintegration of the carbon precursors at 750 °C under atmospheric pressure. The CNS were grown on coated silicon dioxide. The as-synthesized CNS was analysed with Raman spectroscopy which shows carbon quality was found to be 0.92 and 1.01 in PE and RH respectively, indicating good graphitic nature with average diameter at (16.0 to 20.0) ± 0.5 nm. The high intensity ratio is attributed to the defect mode in the CNS. The Field Emission Scanning Microscope (FESEM) analysis shows a warped and randomly oriented structures with an interlayer spacing of about 0.35 nm in the internal structure of most CNS. Furthermore, the level of purity in the graphitic nature of the CNS were obtained with Thermogravimetric Analysis (TGA) technique with 90 % in PE and 50 % in RH. Hence, a fast and cheaper method of synthesizing CNS utilizing microwave energy was demonstrated at 750 °C under atmospheric pressure. Lastly, the presence of catalyst, carbon precursors and plasma are necessary for the microwave heating and synthesis process.